'I want the heart of fierceness to arise within us': maintaining public space to promote HIV-related health with House Ball Community members in an era of gentrification. Issue 4 (2nd April 2020) - Wong, Jeffrey O.; Benjamin, Michael; Arnold, Emily A.
Abstract: The House Ball Community consists of sexual, gender and ethnic minority youth who form family-like houses and compete in balls. Many rely on community-based organisations as venues for socialising and accessing health-related resources. In recent years, urban gentrification has challenged the economic survival of the organisations that serve this community and its members. Between 2016 and 2017, we conducted 45 in-depth interviews with houses and gay families in the San Francisco Bay Area and regular participant observation at community events, including balls. In addition to forcing community organisations to close or move, rising rents have increased housing instability among Ballroom Community members, with some moving to distal locations. Participants felt nostalgia for organisations that provided HIV-related services and hosted balls in previous years, feeling the loss of space keenly. To maintain community and generate employment, the San Francisco Ballroom Community now offers Vogue classes at private dance studios. This allows participants to recruit new house members, welcoming a broader array of individuals into the community than those who have historically participated. However, accessing culturally appropriate sexual health services remains difficult. Health advocates should recognise that community organisations are necessary for diverse youth to build community and access sexual health services.